The Welfare Economics of Heinrich Pesch - Mulcahy, Richard E. (Quarterly Journal of Economics, 1949)
I. Introduction, 342. — II. A goal to be attained: a social science, 343. — III. Objectivity of the goal, 348. — IV. Social philosophy and ethics, 353. — V. A practical and normative science, 357. — VI. Conclusion, 360.